A Task Force Against Local Inflammation and Cancer: Lymphocyte Trafficking to and Within the Skin - Lafouresse, Fanny; Groom, Joanna R. (Frontiers in Immunology, 2018)
The skin represents a specialized site for immune surveillance consisting of resident, inflammatory and memory populations of lymphocytes. The entry and retention of T cells, B cells, and ILCs is tightly regulated to facilitate detection of pathogens, inflammation and tumors cells. Loss of individual or multiple populations in the skin may break tolerance or increase susceptibility to tumor growth and spread. Studies have significantly advanced our understanding of the role of skin T cells and ILCs at steady state and in inflammatory settings such as viral challenge, atopy, and autoimmune inflammation. The knowledge raised by these studies can benefit to our understanding of immune cell trafficking in primary melanoma, shedding light on the mechanisms of tumor immune surveillance and to improve immunotherapy. This review will focus on the T cells, B cells, and ILCs of the skin at steady state, in inflammatory context and in melanoma. In particular, we will detail the core chemokine and adhesion molecules that regulate cell trafficking to and within the skin, which may provide therapeutic avenues to promote tumor homing for a team of lymphocytes.